2012
DOI: 10.1371/journal.pone.0049188
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an In Vitro System Representing the Chicken Gut-Associated Lymphoid Tissue

Abstract: The bursa of Fabricius is critical for B cell development and differentiation in chick embryos. This study describes the production in vitro, from dissociated cell suspensions, of cellular agglomerates with functional similarities to the chicken bursa. Co-cultivation of epithelial and lymphoid cells obtained from embryos at the appropriate developmental stage regularly led to agglomerate formation within 48 hours. These agglomerates resembled bursal tissue in having lymphoid clusters overlaid by well organized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Avian bursa of Fabricius had been identified to play an important role in the development of B lymphocytes as studies showed that the surgical removal of this organ during the embryonic stage of a bird compromised its antibody production thus leading to immunosuppresion [ 11 , 12 ]. The organ serves as an essential site for generation of antibody diversity by gene conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Avian bursa of Fabricius had been identified to play an important role in the development of B lymphocytes as studies showed that the surgical removal of this organ during the embryonic stage of a bird compromised its antibody production thus leading to immunosuppresion [ 11 , 12 ]. The organ serves as an essential site for generation of antibody diversity by gene conversion.…”
Section: Introductionmentioning
confidence: 99%